2004
DOI: 10.1002/path.1685
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of ablative therapy of Barrett's oesophagus

Abstract: Barrett's oesophagus is a major risk factor for developing oesophageal adenocarcinoma. Ablation by argon plasma coagulation (APC) and photodynamic therapy (PDT) is currently under investigation for the removal of metaplastic and dysplastic Barrett's oesophagus. This study examined the effect of ablative therapy on Barrett's oesophagus at cell-cycle and genetic levels. The premalignant potential of residual or recurring Barrett's oesophagus was assessed by p53 immunohistochemistry, Ki67-related proliferative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 33 publications
(48 reference statements)
0
38
0
2
Order By: Relevance
“…In a previous study, we investigated cellular proliferation, aneuploidy and p53 protein overexpression in BE patients after PDT and APC treatment. 45 After an initial downgrading of cell biologic abnormalities, i.e., aneuploidy and increased cellular proliferation, both ablative methods were not able to remove BE completely in a subset of patients. In these patients, biologic abnormalities persisted in both dysplastic and nondysplastic Barrett's epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we investigated cellular proliferation, aneuploidy and p53 protein overexpression in BE patients after PDT and APC treatment. 45 After an initial downgrading of cell biologic abnormalities, i.e., aneuploidy and increased cellular proliferation, both ablative methods were not able to remove BE completely in a subset of patients. In these patients, biologic abnormalities persisted in both dysplastic and nondysplastic Barrett's epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete ablation was obtained in 76% of patients with combined treatment without stricture formation. Residual Barretts epithelium may still harbor molecular aberrations and must, therefore, be considered to be at risk of progression to adenocarcinoma and, therefore, receive further treatment or adequate follow-up [34].…”
Section: Therapeutic Endoscopy Endoscopic Therapy For Early Cancermentioning
confidence: 99%
“…In contrast to PDT, there is no need for patients treated with APC and MPEC to receive a photosensitizing drug, and systemic photosensitization is avoided. Accumulating evidence suggests that APC and MPEC have satisfying safety profiles, with significant complications (e.g., stricture, perforation, bleeding) in fewer than 15% of patients [13,14,[22][23][24][25][26][27][28][29]. This may, in part, be because of the limited depth of coagulation of the techniques compared with other ablative methods [28].…”
Section: Discussionmentioning
confidence: 94%
“…We extracted the results at 6 weeks post-treatment with APC or PDT, respectively. Another study by Hage et al [26] examined the effect of ablative therapy on BE at the cell-cycle and genetic levels; we included this study in our analysis because the endpoints of ablation of BE by histopathology were reported separately. Ragunath et al [27] discovered that APC and porfirmer sodium-induced PDT were equally effective in eradicating Barrett's mucosa but that PDT was more effective in eradicating dysplasia.…”
Section: Argon Plasma Coagulation Versus Surveillancementioning
confidence: 99%